2016
DOI: 10.1073/pnas.1517141113
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress is a barrier to Epstein–Barr virus-mediated B-cell immortalization

Abstract: Epstein-Barr virus (EBV) is an oncogenic herpesvirus that has been causally linked to the development of B-cell and epithelial malignancies. Early after infection, EBV induces a transient period of hyperproliferation that is suppressed by the activation of the DNA damage response and a G1/S-phase growth arrest. This growth arrest prevents long-term outgrowth of the majority of infected cells. We developed a method to isolate and characterize infected cells that arrest after this early burst of proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 57 publications
10
135
0
Order By: Relevance
“…STF-31, used in this study, is one of the promising Glut-1 inhibitors which have been shown to selectively kill renal carcinoma cells (25,43). Interestingly, there are reports showing that high glucose levels also enhance virus infection of host cells, supporting viral replication and maintenance of latency infection (44)(45)(46). Activation of Glut-1 transcription is a novel property of LMP1 not previously reported.…”
Section: Discussionmentioning
confidence: 67%
“…STF-31, used in this study, is one of the promising Glut-1 inhibitors which have been shown to selectively kill renal carcinoma cells (25,43). Interestingly, there are reports showing that high glucose levels also enhance virus infection of host cells, supporting viral replication and maintenance of latency infection (44)(45)(46). Activation of Glut-1 transcription is a novel property of LMP1 not previously reported.…”
Section: Discussionmentioning
confidence: 67%
“…Growth arrested cells have been shown to increase the expression of sestrins leading to AMPK activation and mTORC1 inhibition. 73 Activation of these metabolic stress-signaling pathways suggests that the cells failed to satisfy their high metabolic demands. Providing the cells with cell-permeable metabolites has been shown to increase the number of proliferating cells, demonstrating that metabolic stress contributes to limiting EBV-mediated replicative capacity.…”
Section: Epstein-barr Virus (Ebv) Has Been Shown To Results In An Initialmentioning
confidence: 99%
“…It has also been reported that human gamma-herpesvirus 4 (Epstein-Barr virus, EBV) employ several strategies to interact with autophagic proteins and favor their own survival [23,90,123]. Specific autophagy inhibitors are able to encourage EBV lytic replication and might very well influence its oncogenesis [32].…”
Section: Dsdna Virusmentioning
confidence: 99%